(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: solid pseudopapillary tumor (SPT) of the pancreas is a rare low-level malignant tumor which mainly affects young women. Objective: report the case of an adolescent with a SPT. Clinical case: twelve-year old female adolescent diagnosed with a SPT after an episode of severe abdominal pain on the left hypochondriac region and vomiting. Her medical record did not show a pathological history nor were there findings in the physical examination. The MRI showed a mixed cystic and solid tumor in the caudal portion of the head of the pancreas, which was initially thought to be a SPT. A total surgical resection was performed and the anatomical pathology confirmed the diagnosis. Conclusions: SPT diagnosis should be considered in female adolescents who show a pancreatic tumor and compatible image. A total surgical resection is the Gold Standard regarding the SPT’s therapeutic management.